Effects of lanthanum modification on dielectric properties of Pb(Zr-0.90,Ti-0.10)O-3 ceramics: enhanced antiferroelectric stability - Pelaiz-Barranco, A.; Guerra, J. D. S. [UNESP]; Garcia-Zaldivar, O.; Calderon-Pinar, F.; Araujo, E. B. [UNESP]; Hall, D. A.; Mendoza, M. E.; Eiras, J. A. (Springer, 2008)
Lanthanum modified lead zirconate titanate ceramics with lanthanum content changing from 2 to 6 at% La and a Zr/Ti ratio of 90/10 (PLZT x/90/10) have been analyzed by using X-ray diffraction, dielectric response, differential scanning calorimetry, and ferroelectric hysteresis. An antiferroelectric state was found to be stabilized, whereas the long-range ferroelectric state was disrupted by lanthanum substitution on the lead sites. A ferroelectric state is shown to be stable over an antiferroelectric state for low lanthanum contents in a wide temperature range, where both phases coexist. With the increase of the lanthanum concentration, the long-range coherency of the ferroelectric state is suppressed, i.e., the temperature range of the ferroelectric state stability decreased, disappearing for x > 3 at% La.